2018
DOI: 10.3847/1538-4357/aaa3e7
|View full text |Cite
|
Sign up to set email alerts
|

The HDUV Survey: A Revised Assessment of the Relationship between UV Slope and Dust Attenuation for High-redshift Galaxies

Abstract: We use a newly assembled sample of 3545 star-forming galaxies with secure spectroscopic, grism, and photometric redshifts at z=1.5-2.5 to constrain the relationship between UV slope (β) and dust attenuation (L IR /L UV ≡IRX). Our sample significantly extends the range of L UV and β probed in previous UV-selected samples, including those as faint as M 1600 =−17.4 ( L 0.05 UV *  ) and −2.6β0.0. IRX is measured using stacks of deep Herschel data, and the results are compared with predictions of the I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
293
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 206 publications
(328 citation statements)
references
References 189 publications
30
293
5
Order By: Relevance
“…A similar trend is also observed in high-redshift dusty star-forming galaxies (DSFGs), which have bluer β UV at a given IRX (Oteo et al 2013;Casey et al 2014b;Bourne et al 2017;Chen et al 2017). On the other hand, at high redshift, restoptical-selected galaxies at z 2 (Reddy et al 2018), z 5 Lyman Break Galaxies (Capak et al 2015), and z 7.5 Lyman Break Galaxies (Watson et al 2015) are observed to exhibit redder β UV at given IRX values, which are more consistent with the SMC attenuation curve.…”
Section: Irx-β Uvmentioning
confidence: 59%
“…A similar trend is also observed in high-redshift dusty star-forming galaxies (DSFGs), which have bluer β UV at a given IRX (Oteo et al 2013;Casey et al 2014b;Bourne et al 2017;Chen et al 2017). On the other hand, at high redshift, restoptical-selected galaxies at z 2 (Reddy et al 2018), z 5 Lyman Break Galaxies (Capak et al 2015), and z 7.5 Lyman Break Galaxies (Watson et al 2015) are observed to exhibit redder β UV at given IRX values, which are more consistent with the SMC attenuation curve.…”
Section: Irx-β Uvmentioning
confidence: 59%
“…In the right panel of Figure 4, we compare our findings with several results in the literature. These include stacking analyses of single dish sub-mm telescope data, Spitzer MIPS, and/or Herschel SPIRE data using rest-frame UV/Optical galaxy selections (Álvarez-Márquez et al 2016;Koprowski et al 2018;Heinis et al 2014;Whitaker et al 2017;Reddy et al 2018). Additionally, we show the stacking results of ALMA data (Bouwens et al 2016;McLure et al 2018), which utilise a smaller field of view, but have a higher angular resolution than the previous observations.…”
Section: Comparison With Irx-m * Relations From Previous Analysesmentioning
confidence: 78%
“…Because some of the emission lines have high equivalent widths, we have corrected the photometry by subtracting the contribution from the emission 2003). As suggested by Reddy et al (2018) for highredshift, low-mass galaxies, we use the SMC dust extinction curve (Gordon et al 2003) with A V values varying between 0.0 − 2.0. We fix the metallicity at 0.2 Z and the redshift at the spectroscopic value.…”
Section: Stellar Mass and Agementioning
confidence: 99%